060 The practice and perception of transvenous lead extraction in the UK: lessons from a nationwide survey. (16th May 2012) - Sohal, M; Williams, S E; Chen, Z; Bostock, J; Hamid, S; Patel, N; Bucknall, C; Gill, J S; Rinaldi, C A
Abstract : Introduction: The rate of cardiac implantable electronic device (CIED) implantation in the UK has been rising consistently and this trend is likely to continue. We sought to establish the nature of lead extraction practice in the UK. Methods: The Heart Rhythm UK (HRUK) directory of members was used to compile a list of potential respondents for the survey. A link to the Survey Monkey online tool was sent with HRUK administrative support and responses were collated prior to analysis. The survey consisted of 21 questions and all results were anonymous. Results: In total, 29 responses were received and of these 24 (82.8%) regularly performed trasnvenous lead extractions. The vast majority (82.8%) were electrophysiologists. Most operators performed up to 25 procedures per year (Abstract 060 figure 1A ). Most procedures were performed in the EP lab with on-site surgical cover present at all but one site. The nature of surgical cover was generally informal (Abstract 060 figure 1B ). The perceived commonest reason for extraction was a combination of infection/erosion and sepsis (93.1%). After a failed attempt at manual traction the most widely used method of extraction was to use a mechanical dissection sheath (65.5%) followed by the use of a laser sheath (21.1%). Peri- and post-procedure temporary pacing mostly utilised either a standard temporary pacing wire or an externalised permanent pacemaker device. Active fixation endocardial pace/sense leads were generally perceived the easiest and safest leads to extract while dual coil defibrillator leads and active fixation coronary sinus leads were perceived the most difficult and associated with the greatest risk (Abstract 060 figure 2A, B ). The perception of minor and major complication rates and the risk of death increased with device complexity. The risk of minor complications was perceived to be 4% or less by the majority of respondents across the device range. The same measure for major complications and death was 2% and 1% respectively. Conclusions and Implications: Transvenous lead extraction is becoming increasingly common and most UK operators who responded to our survey perform 25 cases or fewer per annum. Surgical stand-by support was mostly informal but a significant minority of cases were performed in an operating theatre with a surgeon present. The perceived risk of the procedure was broadly in line with widely published figures internationally. The 2009 Heart Rhythm Society consensus document made a series of recommendations with regards to training, case volume and stand-by surgical support. It is suggested that a minimum of 20 cases per year be performed by each operator and that a cardiothoracic surgeon be physically on site and capable of performing an emergent procedure promptly. Accordingly, increased operator caseload and closer links between EP extractors and surgeons should be seen as achievable goals.